Arguing Skillfully with Argument-Driven Inquiry Science Textbooks - Wirawan Fadly*; Miaturrohmah Miaturrohmah (Jurnal Pendidikan Sains Indonesia, 2021)
Argumentation skills have an important role in 21st-century learning because it can facilitate constructing the relationship between theory and understanding the concept of science. The development of textbooks based on argumentation skills can bridge science theories and ideas, especially with the Covid-19 pandemic, limiting social contact between communities and students so that they have to work and study from home. Textbooks can be a solution to assist students to learn independently. This study aims to determine the characteristics, practicality, and effectiveness of the developed argument-driven inquiry textbook (ADI). The research was conducted at MTsN 6 Ponorogo using the Research and Development (RD) method. Testing the practicality and effectiveness of textbooks was carried out using a randomized control group pretest-posttest design. The number of research samples consisted of 124 students taken through random sampling techniques divided into experimental and control classes. Data were obtained from questionnaires, and argumentation skills tests were analyzed using quantitative descriptive and qualitative descriptive to determine practicality, and inferential statistics (t-test) to evaluate the effectiveness of the textbooks being developed. The results showed that ADI-based textbooks: 1) have the characteristics of being able to encourage students to argue critically and be able to construct students' logic and creativity in relating environmental problems, scientific concepts, and scientific paradigms through multi-disciplinary integration; 2) has a practicality level of 84%, which means that the contents of the book are very good at motivating students to learn, relevant to the material, and easy to understand from the material and language aspects; 3) effective in improving students' argumentative skills is better than classes that are not based on ADI (α = 0.05) with an increase in the moderate category (N-Gain = 47.17%).